Tyta Liwiusza "Dzieje rzymskie" hrabiego Ossolińskiego. Pierwszy polski przekład Ab urbe condita = The first Polish translation of Livius' "Ab urbe condita" by count Józef Maksymilian Ossoliński - Dziuba, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is devoted to the first, incomplete, Polish translation of Livy's Ab Urbe condita. The translation was done by the blind count Józef Maksymilian Ossoliński, alumnus of Jesuitic Collegium Nobilium in Warsaw. Considering the comments in the preface directed to a reader, the translator appears to be a mindful person aware of difficulties of his work. Nevertheless, his "translatoric operations" fully coincide with the translation theory.
Keywords: Ossoliński, Józef Kajetan Piotr Maksymilian (1748-1826); Titus Livius (59 p.n.e.- 17 n.e.); oświecenie - literatura; historiografia polska - 18 w.; tłumaczenia; historiography; Polish Enlightenment; translations